2009
DOI: 10.4314/tjs.v33i1.44278
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and dyes biodegradation potential of crude lignolytic enzymes from white-rot fungus crepidotus variabilis isolated in coastal Tanzania

Abstract: Lignocellulosic enzymes from Crepidotus variabilis collected from mangrove forests of coastal Tanzania were investigated by using standard methods, and their ability to degrade aromatic compounds were elucidated. The fungal crude enzyme filtrates had maximum laccase (Lac), lignin peroxidase (LiP) and manganese peroxidase (MnP) activities of 70 U/mL, 16 U/mL and 8, U/mL respectively. The crude enzyme extracts were able to oxidize rhemazol brilliant blue-R (RBB-R) dye, phenol, "-naphthol and pyrogallol. Also, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…After incubation at 28 ± 2°C, for 7 days, the production of laccase was observed using 0·1 mol l −1 α‐naphthol drop test (Okino et al . 2000; Mtui 2007).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After incubation at 28 ± 2°C, for 7 days, the production of laccase was observed using 0·1 mol l −1 α‐naphthol drop test (Okino et al . 2000; Mtui 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The production of peroxidases was observed using 1% pyrogallol drop test (Okino et al . 2000; Mtui 2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of biodegradation reduced the values within recommended values which confi rmed the signifi cance of this process. High BOD and COD made aquatic life diffi cult while reduction in these values made water suitable for aquatic life (Elkassas and Mohamed 2014, Mtui andNakamura 2008, Porwal et al 2015). Luczkiewicz et al in 2011, reported the reduction in COD, BOD and Total Suspended Solid (TSS) of wastewater treated with various physical techniques but the ratio of reduction (a difference between initial value and fi nal value) was low compared to our results during current study.…”
Section: Determination Of Bod and Cod Of Bio-treated Textile Effl Uentsmentioning
confidence: 99%